Macro-economic determinants of penal policy: estimating the unemployment and inflation influences on imprisonment rate changes in the United States, 1948-1985 - Lessan, Gloria T. (Crime, law and social change, 1991)
Conflict theory proposes that systemic economic distress generates problem populations which require control via palliative and coercive means. Most previous research has concentrated on examining the unemployment-imprisonment relationship. A review of the literature suggests that other structural conditions that generate marginalization as well as the state's placative control must be considered in order to understand the linkage between economic-fiscal forces and penal policy. Using annual time-series data for the period 1948-1985, the present paper examines the extent to which changes in inprisonment rates reflect (a) governmental attempts to offset the threat of unemployment and inflation and (b) fiscal limitations placed by state expenditures on placative controls. The results indicate support for the conflict thesis, with inflation rates and annual fluctuations in black and white male unemployment rates exerting an independent positive effect upon imprisonment-rate changes, after controlling for variations in violent crime rates, prison capacity, and age structure. Possible reasons for the lack of evidence regarding trade-offs between state's placative and coercive policies are discussed and suggestions for further research are noted. *** DIRECT SUPPORT *** AW502010 00003